Echocardiographic evaluation of left ventricular diastolic dysfunction in recently diagnosed type 2 diabetes mellitus - Jain, Swapnil; Nawal, C. L.; Singh, Amandeep; Chejara, Radhey Shyam; Barasara, Sagar; Marker, Sebastian (International Journal of Research in Medical Sciences, 2018)
Background: Diastolic dysfunction in patients suffering from diabetes mellitus represents an earlier stage in the natural history of cardiomyopathy. This study was done to assess the left ventricular diastolic dysfunction in recently diagnosed (<5yr) Type 2 Diabetes Mellitus by Echocardiography and also to determine association of glycemic status (by HBA1c levels) with left ventricular diastolic dysfunction (LVDD). Methods: An observational descriptive study involving 100 diabetic patients, taken on first come first serve basis after applying inclusion and exclusion criteria. In all the subjects, other than routine investigations, HbA1c was estimated and echocardiography was done to evaluate LVDD. Results: Mean value of HbA1c in the study was 8.31+ 1.408 %. 63 out of 100 subjects had LVDD. There was significant positive correlation between HbA1c and LVDD (p value <0.001). As HbA1c increased, severity of LVDD increased. In this study, as BMI increased, HbA1c and LVDD increased & both findings were statistically significant (p value =0.001). Conclusion: Our study indicates that myocardial damage in patients with diabetes affects diastolic function before systolic function &higher HbA1C level is strongly associated with presence of LVDD. Patients should be advised strict control of diabetes in order to reduce the risk for developing LVDD which is a precursor for more advanced disease. Keywords: Diabetes mellitus, Diastolic dysfunction, BMI, HbA1c